Maturação fisiológica de sementes de maxixe (Cucumis anguria L.) - Medeiros, Maria Aparecida de (2009)
This work was aimed at to evaluate the physical and physiological changes along the maturation process of gherkin (Cucumis anguria L.) seeds, which are important aspects with regard to the production of high quality seeds and minimization of their deterioration in the field. The experiment was carried out at the Experiment Garden Facility and the analyses performed at the Seed Analysis Laboratory, Plant Science Department, Universidade Federal Rural do Semi-Árido (UFERSA). The seeds were collected from cultivar 'Do Norte' fruits at five-day intervals, from the 15th to the 40th day after anthesis. It was utilized a completely randomized experiment with six treatments (fruit ages) and four replications. The seed physiological quality was evaluated through humidity content, dry mass, germinability, vigor, germination speed index, accelerated aging, and electric conductivity. The maximum physiological quality was found in seeds collected from fruits as old as 30 days after anthesis, but the best time to harvest the fruits is when they reach 35 to 40 days after anthesis.